Pemanfaatan Google Classroom dalam Menumbuhkan Kreativitas Peserta Didik pada Pembelajaran Sejarah di Masa Pandemi - Euis Nela; Nana Supriatna; Leli Yulifar (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2022)
This research is motivated by government instructions, namely learning from home (BDR), with these instructions, teachers are still confused about the right media, methods and strategies for online teaching and learning activities, so that learning activities are still teacher-centered resulting in the learning process feeling less fun and does not motivate students to learn so that they have not been able to grow creativity, both creative thinking and creativity. The general purpose of writing is to find out the use of Google Classroom in fostering student creativity. The method used in this research is descriptive verification. Based on the results of this study, it is known that the teacher has made a good lesson plan, then the application of Google Classroom can create a virtual classroom that creates a more effective communicative environment for teachers and students; The learning process using Google Classroom has been integrated with the use of the Creative Learning approach and the Video Critical Learning (VCL) learning model as well as lecture, assignment, discussion and question and answer methods. Google Classroom has also been integrated with Youtube, namely in the use of the chat feature in the Google Classroom forum/stream, this feature is useful because it can be a means of interaction between teachers and students or students with other students. In this feature students can express their creative opinions, can send video presentations that are integrated with Youtube as a result of their work to be watched, analyzed and commented on/criticized by other students; The use of Google Classroom-based LMS in fostering students' creativity has had a pretty good impact.